2017
DOI: 10.1177/1071100717702461
|View full text |Cite
|
Sign up to set email alerts
|

Value of Tourniquet Use in Anterior Ankle Arthroscopy: A Randomized Controlled Trial

Abstract: Level I, prospective randomized controlled trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Because of increased swelling and skin tension, a persistent ischemia may occur on the skin and subcutaneous tissue, which may have predisposed those patients to higher amount of pain and wound healing complications [24]. However, use of a tourniquet did not affect the functional outcome, as the results of AOFAS score was similar between the groups, this outcome is consistent with the study performed by Dimnjakovic et al [8].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Because of increased swelling and skin tension, a persistent ischemia may occur on the skin and subcutaneous tissue, which may have predisposed those patients to higher amount of pain and wound healing complications [24]. However, use of a tourniquet did not affect the functional outcome, as the results of AOFAS score was similar between the groups, this outcome is consistent with the study performed by Dimnjakovic et al [8].…”
Section: Discussionsupporting
confidence: 85%
“…Zaidi et al conducted a prospective nonrandomized study to explore the effects of tourniquet use in ankle arthroscopy, they noted that tourniquet use showed no clinical disadvantages in regard to duration of operation, maximum intraoperative uid pressures or visibility, and announced ankle arthroscopy was possible without the use of a tourniquet [22]. Dimnjakovic et al also found that in ation of a tourniquet did not result in increased duration of operation, maximum intraoperative uid pressures or visibility after anterior ankle arthroscopy [8]. Our outcomes corresponded well to both studies above, in which the results of surgical duration were comparable between two groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most recent consecutive 23 procedures were performed without the use of the tourniquet because of good experience developed during years with ankle arthroscopy without the tourniquet. 12 No issues were observed during the procedures. No skin disorders or infections were encountered after the operation.…”
Section: Resultsmentioning
confidence: 99%
“…However, the use of tourniquet is potentially risky; so, working with tourniquet requires care and expertise. Some studies have shown that tourniquet application is not necessary during minimally invasive such as Arthroscopic ankle surgery [5,6]. Tourniquet application has potential risks of improper and even proper use during lower limb surgery, including muscle injury, functional weakness and reduced muscle strength, joint stiffness and postoperative swelling [7,8].…”
Section: Introductionmentioning
confidence: 99%